Analisis Efisiensi Lumen Lampu Berdasarkan Nama Ruangan di IGD Sidoarjo (R.T. Notopuro) - Miftahur Rohim; Cilda Thesisa; Ikhwanuddin Ikhwanuddin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This research aims to analyze the efficiency of lamp lumen usage based on the function and name of rooms in the Emergency Room (ER) of RSUD Sidoarjo (R.T. Notopuro). Effective and efficient lighting is a critical factor in supporting medical performance and patient comfort. Each room in the ER has different lighting needs, depending on the activities and functions, such as Surgical Treatment Room, Isolation Room, Asthma Room, and Back Corridor. The method used is a descriptive qualitative approach with direct observation and documentation techniques, along with light intensity measurements using a luxmeter. The data were analyzed by comparing the actual lumen values with lighting standards based on Indonesian National Standard (SNI) and clinical room requirements. The results showed that most rooms did not fully meet the required lighting efficiency standards, especially in critical care and transitional areas. The mismatch between the number of lamps, lamp types, and room function was identified as the main cause of inefficiency.